Legal Consequences of Transfer of Home Ownership Loans without Creditors' Permission - Ramadhani, Rahmat (International Journal Reglement & Society (IJRS), 2020)
The transfer of mortgage loans is carried out without prior approval from the bank as the debtor and is carried out under an underhand loan agreement between the parties. This research uses normative juridical legal research methods (normative research), namely legal research conducted by examining library materials or secondary data. The research specification in this paper is descriptive analytical research. Based on the results of the research, it is known that the transfer demands several things that need to be known, namely changes or additions to the provisions of this agreement can only be done after there is an agreement and it is done in writing that is signed by the creditor and debtor, the debtor is not entitled to transfer or transfer rights and obligations. part or all based on this credit agreement to other debtors without prior written approval from the creditor, the creditor can transfer or transfer part or all of the rights and obligations under the credit agreement to other creditors with prior written notification to the debtor.